Seasonal variation of underwater sound propagation in the Beibu Gulf - Feihong Zeng; Feihong Zeng; Lingling Xie; Lingling Xie; Lingling Xie; Mingming Li; Mingming Li; Mingming Li; Qiang Li; Qiang Li; Qiang Li; Simeng Liu; et al. (Frontiers in Marine Science)
Variations in the underwater sound speed significantly influence sound propagation in the ocean, thereby impacting both underwater navigation systems and a substantial portion of marine organisms reliant on sound. This study utilizes cruise data from the Beibu Gulf during the summer and winter of 2023–2024 to explore the seasonal variations in temperature and salinity affecting the sound speed distribution and characteristics of sound propagation. Results indicate significant differences in the sound speed on either side of the 30-m isobath in the Beibu Gulf, with pronounced changes corresponding to seasonal temperature and salinity variations. In summer, the sound speed in the Beibu Gulf exhibits a north-high–south-low pattern. In areas shallower than 30 m, the sonocline is predominantly positive or absent, whereas, in deeper areas, it is mainly negative. During winter, there is a south-high–north-low pattern in sound speed across the Beibu Gulf, with pronounced sound speed extremes in areas shallower than 30 m. Sound propagation simulations based on the Beibu Gulf sound-speed field reveal that sounds at the 100-Hz frequency propagate significantly farther and cover larger areas in depths less than 30 m compared to deeper areas. In summer, this phenomenon is more pronounced than in winter due to the presence of positive sonoclines. The results have significant implications for target detection, underwater acoustic communication, and the protection of aquatic animals that rely on underwater sound for survival in the Beibu Gulf.